Geographical variation in the echolocation calls of bent-winged bats, Miniopterus fuliginosus - Zhang, Chunmian; Jiang, Tinglei; Lu, Guanjun; Lin, Aiqing; Sun, Keping; Liu, Sen; Feng, Jiang (Zoology (Jena), 2018)
•We studied geographical variation in echolocation calls of bent-winged bats (Miniopterus fuliginosus).•The peak frequency of seven colonies was similar, while only one colony was significantly higher than the others.•This variation patterns in echolocation calls may not be driven by genetic drift of M. fuliginosus.•The strong selective pressure induced by background noise may lead to acoustic divergence between JXT and the other colonies. Evolutionary biologists had a long-standing interest in the evolutionary forces underlying geographical variation in the acoustic signals of animals. However, the evolutionary forces driving acoustic variation are still unclear. In this study, we quantified the geographical variation in the peak frequencies of echolocation calls in eight Miniopterus fuliginosus bat colonies, and assessed the forces that drive acoustic divergence. Our results demonstrated that seven of the colonies had very similar peak frequencies, while only one colony was significantly higher than the others. This similarity in echolocation call frequency among the seven colonies was likely due to frequent dispersal and migration, leading to male-mediated infiltration of nuclear genes. This infiltration enhances gene flow and weakens ecological selection, and also increases interactions in the presence of conspeciﬁcs. Significant correlations were not observed between acoustic distances and morphological distances, climatic differences, geographic distances or mtDNA genetic distances. However, variation in acoustic distances was significantly positive correlated with nDNA genetic distance, even after controlling for geographic distance. Interestingly, the relationship between call divergence and genetic distance was no longer significant after excluding the colony with the highest call frequency, which may be due to the minimal genetic distance among the other seven colonies. The highest frequencies of echolocation calls observed in the one colony may be shaped by selection pressure due to loud background noise in the area. Taken together, these results suggest that geographic divergence of echolocation calls may not be subject to genetic drift, but rather, that the strong selective pressure induced by background noise may lead to acoustic and genetic differentiation between JXT and the other colonies.